2011
DOI: 10.1007/s00401-011-0831-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-synaptic cortical cholinergic deficits are proportional to amyloid plaque presence and density at preclinical stages of Alzheimer’s disease

Abstract: Amyloid imaging has identified cognitively normal older people with plaques as a group possibly at increased risk for developing Alzheimer’s disease-related dementia. It is important to begin to thoroughly characterize this group so that preventative therapies might be tested. Existing cholinotropic agents are a logical choice for preventative therapy as experimental evidence suggests that they are anti-amyloidogenic and clinical trials have shown that they delay progression of mild cognitive impairment to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 81 publications
(130 reference statements)
7
55
0
2
Order By: Relevance
“…There is ample evidence for a cholinergic dysfunction associated with memory impairment (Bartus et al, 1982), in particular with AD (Auld et al, 2002), as heralded by the observations that Ab can decrease the evoked release of acetylcholine from hippocampal slices (Kar et al, 1996) and that there is a decreased ability to trigger acetylcholine release in cortical samples from demented individuals (Sims et al, 1983). Several studies in humans and in animal models of AD showed that the modification of the cholinergic system is an early event, already measurable at pre-symptomatic stages of AD (Watanabe et al, 2009;Potter et al, 2011;Zhang et al, 2012; but see Davis et al, 1999). However, there is some debate as to whether the changes are compensatory or part of the disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence for a cholinergic dysfunction associated with memory impairment (Bartus et al, 1982), in particular with AD (Auld et al, 2002), as heralded by the observations that Ab can decrease the evoked release of acetylcholine from hippocampal slices (Kar et al, 1996) and that there is a decreased ability to trigger acetylcholine release in cortical samples from demented individuals (Sims et al, 1983). Several studies in humans and in animal models of AD showed that the modification of the cholinergic system is an early event, already measurable at pre-symptomatic stages of AD (Watanabe et al, 2009;Potter et al, 2011;Zhang et al, 2012; but see Davis et al, 1999). However, there is some debate as to whether the changes are compensatory or part of the disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These changes thus may reflect a compensatory response to maintain basocortical cholinergic function given that loss of pre-synaptic receptors usually results in compensatory up-regulation of post-synaptic receptors [35]. Alternatively, the relative preservation or increase may also be the result of a postulated bidirectional modulatory effect between beta amyloid and M1 receptors in the frontal and parietal areas [41].…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic changes may manifest even at the preclinical stage [41], although others have demonstrated that in early stages of AD, cholinergic neurons in the basal forebrain are relatively preserved [15,21]. Nevertheless, remediation of cholinergic function, in the form of cholinesterase inhibitors (AChEIs), has been the mainstay of symptomatic treatment in AD for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Previously defined as the manifestation of deteriorating brain functions over time due to cell deaths in the brain caused by neurodegeneration or any other disease [3], according to recent research dementia is not primarily caused by neuronal cell death/loss, but by dysfunction and loss of synapses [4] in AD [5] and in α-synucleinopathies [6]. Other causes include cholinergic neuronal and axonal abnormalities [7,8], as well as pre-and postsynaptic cortical cholinergic deficits also occurring in early AD [9]. These changes due to disconnection of major nervous circuitries causing default networks [10][11][12][13] have been demonstrated in vivo in early AD [14], suggesting that disease progress is transmitted by neuronal pathways [15].…”
Section: Introductionmentioning
confidence: 99%